Determinants of Customer Trust: A Study on Safety, Ease-of-use, and Perceived usefulness of Herbal Products of Kuku Bima Ener-G - Siti Nur Halizah; Eli Retnowati; Didit Darmawan; Rafadi Khan Khayru; Fayola Issalillah (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
People have alternative treatments and treatments through traditional techniques and herbal remedies. They have attitudes and beliefs about herbs to be able to overcome complaints of certain diseases or just treatment of the body. Pharmaceutical companies in the traditional medicine group are growing. This makes the market share more competitive, because there are so many products for indications based on complaints about disease disorders or increasing body vitality. Related to this, it is very important to know the factors that influence customer trust in herbal medicinal products. This study aims to determine significantly the safety, ease-of-use, and perceived usefulness of Kuku Bima Energi Herbal on customer trust. The object of this research is aimed at consumers of Kuku Bima Energi Herbal. In this study using 100 respondents. Data were analyzed using regression analysis. This study resulted in the finding that safety has a significant effect on customer confidence in Kuku Bima Energi Herbal. In line with ease-of-use of having a significant effect on customer trust Kuku Bima Energi Herbal. Likewise, the perceived usefulness has a significant effect on customer trust, Kuku Bima Energi Herbal.